Предмет: Математика,
автор: Arboletomania
Упростите выражения: (a+b)(a-b)-(a2-b2)
перед a и b квадрат 2
2) 3a2-a(a-b)
перед 3a квадрат 2
Ответы
Автор ответа:
0
(a+b)(a-b)-(a^2-b^2)=a^2-b^2-a^2+b^2=0; 3a^2-a(a-b)=3a^2-a^2+ab=2a^2+ab=a(2a+b). вот решение, если правильно понял условие.
Похожие вопросы
Предмет: Английский язык,
автор: Аноним
Предмет: Английский язык,
автор: MrBinN19952001
Предмет: Українська мова,
автор: dgetiX
Предмет: География,
автор: oliviya2012
Предмет: История,
автор: Алина8877